An unusual case of intestinal obstruction due to Meckel’s diverticulum with vitelline cyst: case report - khan, Wajiha; Mehwish Mooghal; Asrar Ahmad; Syeda Sanila Aijaz; Yusra Iqbal (Journal of the Pakistan Medical Association, 2022)
Meckel's diverticulum (MD)1, the most common congenital anomaly of the gastrointestinal tract, occurs in 2% of the population with males being more symptomatic than females. In this case, a 32-year-old male presented with sudden onset colicky abdominal pain, bilious vomiting, and absolute constipation. Emergency laparotomy was done on his virgin abdomen, as a result MD and vitelline cyst along with a fibrous cord connecting the two were identified. Knotting of an ileal loop around this cord had resulted in intestinal obstruction. Meckel’s diverticulectomy, along with cord resection, was carried out. The patient made smooth recovery and was discharged on the fifth postoperative day with no complications. The importance of this study is to highlight the case of symptomatic MD in an adult male as it can be a cause of intestinal obstruction and should always be considered in a patient presenting with symptoms of intestinal obstruction.